2021
DOI: 10.3390/molecules26133904
|View full text |Cite
|
Sign up to set email alerts
|

Review of Functional and Pharmacological Activities of Berries

Abstract: Functional plant-based foods (such as fruits, vegetables, and berries) can improve health, have a preventive effect, and diminish the risk of different chronic diseases during in vivo and in vitro studies. Berries contain many phytochemicals, fibers, vitamins, and minerals. The primary phytochemicals in berry fruits are phenolic compounds including flavonoids (anthocyanins, flavonols, flavones, flavanols, flavanones, and isoflavonoids), tannins, and phenolic acids. Since berries have a high concentration of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 216 publications
0
72
2
2
Order By: Relevance
“…The high activity of these extracts may be explained simply by their chemical composition. According to Golovinskaia et al [16], raspberry extracts should contain polyphenols, anthocyanins and flavonols. According to Harscoat-Schiavo et al [6], pomegranate extracts should include anthocyanins, proanthocyanidins and hydrolysable tannins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high activity of these extracts may be explained simply by their chemical composition. According to Golovinskaia et al [16], raspberry extracts should contain polyphenols, anthocyanins and flavonols. According to Harscoat-Schiavo et al [6], pomegranate extracts should include anthocyanins, proanthocyanidins and hydrolysable tannins.…”
Section: Discussionmentioning
confidence: 99%
“…These mixtures contain active substances from both extracts. The rosemary extract should include ursolic acid [12,13] and the raspberry extract should contain tannins [16]. Alvarez-Martínez et al [28] proved that tannins and ursolic acid revealed multifactorial activity, rather than one activity mechanism, with pleiotropic effects at various levels also being observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants that contain large quantities of proanthocyanins include blackberries ad hawthorn berries. The bioavailability of proanthocyanidins is primarily influenced by polymerization, which is rendered insignificant in the gastric tract ( Golovinskaia and Wang 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…and other bioactive substances such as vitamin A, folates, and vitamin K [ 74 ]. Nevertheless, they are still needed for phenolic compounds in some concrete cases such as berries [ 75 ]. In other fruits, the bioavailability has recently been reviewed for apples [ 76 ] and tomatoes [ 77 ].…”
Section: Fruits and Their Antioxidant Activitymentioning
confidence: 99%